The Immunological Impact of IL-1 Family Cytokines on the Epidermal Barrier - Macleod, Tom; Berekmeri, Anna; Bridgewood, Charlie; Stacey, Martin; McGonagle, Dennis; Wittmann, Miriam (Frontiers in Immunology, 2021)
The skin barrier would not function without IL-1 family members, but their physiological role in the immunological aspects of skin barrier function are often overlooked. This review summarises the role of IL-1, IL-18 and IL-36 cytokines in the skin. We focus on novel aspects of their interaction with commensals and pathogens, the important impact of proteases on cytokine activity, on healing responses and inflammation limiting mechanisms. We discuss IL-1 family cytokines in the context of IL-4/IL-13 and IL-23/IL-17 axis-driven diseases and highlight consequences of human loss/gain of function mutations in activating or inhibitory pathway molecules. This review highlights recent findings that emphasize the importance of IL-1 family cytokines in both physiological and pathological cutaneous inflammation and emergent translational therapeutics that are helping further elucidate these cytokines.